Управління економічною стійкістю промислового підприємства - Руденко, Олександр Михайлович; Rudenko, Oleksandr Mykhaylovych (Ірпінь, 2024)
У роботі досліджується аналіз та оцінка системи управління економічною стійкістю підприємства.

The work examines the analysis and assessment of the management system of the economic sustainability of the enterprise.
Management of the economic stability of an industrial enterprise
Keywords: підприємство; економічна стійкість підприємства; показники економічної стійкості; управління економічною стійкістю; enterprise; economic sustainability of the enterprise; indicators of economic sustainability; management of economic sustainability